Taxonomic distribution of neoplasia among non-domestic felid species under managed care (2020)
As evidenced by numerous case reports from zoos, neoplasia in felids is common, but most reports are limited to Panthera species in North America or Europe. In order to obtain a wider epidemiologic understanding of neoplasia distribution, necropsy records at seven facilities (USA, Mexico, Colombia, Peru, and Brazil) were evaluated. In contrast to others, this study population (195 cases, 16 species), included many non-Panthera felids. Overall neoplasia prevalence was 28.2% (55/195). Panthera species had a higher prevalence of neoplasia than non-Panthera species (52.5%; vs. 13.0%). Lions (66.7%), jaguars (55.0%), and tigers (31.3%) had the highest species-specific prevalence of neoplasia. Neoplasms in Panthera species were more frequently malignant than in non-Panthera (86.1% vs. 55.6%). The systems most commonly a_ected were the reproductive, hematolymphoid, and respiratory. The range of management conditions and more varied genetic backgrounds support a robust taxonomic pattern and suggest that the reported propensity for neoplasia in jaguars may have a genetic basis at a taxonomic level higher than species, as lions and tigers also have high prevalence. Given the high prevalence of neoplasia and high likelihood of malignancy, routine medical exams in all nondomestic felids, but Panthera species in particular, should include thorough assessments of any clinical signs of neoplasia.